2002
DOI: 10.1021/ja026342h
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis for Induction of VanB Resistance

Abstract: Because teicoplanin and vancomycin are the last line of defense for many bacterial infections, the emergence of resistance to glycopeptide antibiotics in enterococci and streptococci has aroused concern. Despite their similarity in terms of structure and mechanism of action, vancomycin induces the expression of genes that leads to bacterial resistance, and teicoplanin does not. We have used a combination of chemical and enzymatic methods to produce sets of vancomycin and teicoplanin analogues that allow us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 15 publications
3
59
0
1
Order By: Relevance
“…Given that P. aeruginosa employs AHL 1 as the principal autoinducer and the known bactericidal activity of tetramic acids, we hypothesized that compound 4 could have a biological function in the context of bacterial viability. We were guided by the observation that lipid-substituted antibiotics have been shown to localize near the cell membrane of Gram-positive bacteria (10). Indeed, significant antibacterial activity was observed against all tested Gram-positive bacterial strains in the presence of 4 after overnight incubation (Table 2), whereas no toxicity was observed against P. aeruginosa or other tested Gram-negative bacteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that P. aeruginosa employs AHL 1 as the principal autoinducer and the known bactericidal activity of tetramic acids, we hypothesized that compound 4 could have a biological function in the context of bacterial viability. We were guided by the observation that lipid-substituted antibiotics have been shown to localize near the cell membrane of Gram-positive bacteria (10). Indeed, significant antibacterial activity was observed against all tested Gram-positive bacterial strains in the presence of 4 after overnight incubation (Table 2), whereas no toxicity was observed against P. aeruginosa or other tested Gram-negative bacteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…∆S conf correlates, however, to little enhancement of the activity of dimeric Vans against vancomycin-sensitive strains and the less resistant VRE (VanC), which has been observed in other systems of divalent Vans, 16,17,34 suggesting the enhancement of the activity of dimeric Vans may depend on the composition of peptidoglycan precursors produced by the strains. 43 …”
Section: Resultsmentioning
confidence: 99%
“…We have previously made many glycopeptide derivatives containing lipid substituents at different positions, either on the aglycone or on the carbohydrates (7,(33)(34)(35)(36). We have found that the potency of most lipid-linked glycopeptides decreases dramatically when their peptide-binding pockets are damaged, implying that peptide binding is important for activity.…”
Section: Discussionmentioning
confidence: 99%